Biological accretion of some weighty metals in tilapia fish relevant to their concentration in water and sediment of Wadi Hanifah, Saudi Arabia - Gulza, Shafiq; Gohar, Rizwan; Yhasmine, Wasim (Advances in Aquaculture and Fisheries Management, 2013)
Concentrations of some heavy metals (Pb, Cd, Hg, Cu and Cr) were determined in water, sediment and tissues of tilapia fish collected from Wadi Hanifah during summer 2010. The concentrations of the heavy metal in water were within the international permissible level. Cu had the highest accumulating level in fish whilst Hg had the lowest. The transfer factors of all metals in fish from water were greater than those from sediments. This led to the conclusion that fish bioaccumulation with these metals was from water. Heavy metals under study in the edible parts of tilapia were within the safety permissible level for human use